Research on methods of workers’ context description in mines - Shimin FENG; Enjie DING; Zhongyu LIU; Xiao YU; Lei MENG; Zhikai ZHAO (物联网学报)
The worker’s unsafe behavior is the key cause of mine accidents.The human activity is closely related with the context.Ontology is widely used in computer science in the field of information exchange and knowledge sharing,which contains complex structures and various semantics.Firstly,the research on the description of the miners’ situational information in the mining field was summarized.It introduced the general situation in the field of the Internet of things.The importance and necessity of the description of the state information of mine personnel was presented.It introduced the research background,including semantic web,context description and knowledge representation.After that,the method of information description of mine personnel was described.The ontology model was proposed based on oneM2M international technical specifications.In order to construct this ontology,it was drawed on some of the core concepts of oneM2M Base Ontology.The concept classes,attributes and relationships that are specific to the information description of mine personnel were put forward.The context description of mine personnel proposed was aimed at achieving the purposes of specification information description,data semantic labeling,knowledge sharing and reuse.Finally,the conclusions were drawn and the prospect of using the ontology method for context perception and the miners’ unsafe behavior recognition was presented.